1999
DOI: 10.1007/bf02783878
|View full text |Cite
|
Sign up to set email alerts
|

Zinc coadministration attenuates melatonin’s effect on nitric oxide production in mice

Abstract: Both melatonin (MEL) and zinc (Zn) are considered beneficial for anti-immunosenescence. MEL's effects on immune functions are partly attributed to an interaction with Zn. However, the augmentation of or interference with MEL's effects by coadministration of Zn remains unclear. In this study, adult older mice received either MEL (10 microg/mL), Zn (22 microg/mL), MEL+Zn, or null supplementation from drinking water for 3 mo. The results showed that treated mice, irrespective of the type of added chemicals, had h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…In fact, it has been established that melatonin supplementation has decreased the serum nitrite and nitrate levels. 13 However, it is stated that melatonin and zinc supplementation negatively affects the suppression on NO levels formed by melatonin. Although NO is defined as a mediator of especially the post I/R glutamate toxicity, it has been determined that melatonin supplementation decreases the brain NO production by suppressing NO synthetase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, it has been established that melatonin supplementation has decreased the serum nitrite and nitrate levels. 13 However, it is stated that melatonin and zinc supplementation negatively affects the suppression on NO levels formed by melatonin. Although NO is defined as a mediator of especially the post I/R glutamate toxicity, it has been determined that melatonin supplementation decreases the brain NO production by suppressing NO synthetase.…”
Section: Discussionmentioning
confidence: 99%
“…12 Application of zinc together with melatonin suppresses the effect that melatonin creates in NO production. 13 It was reported that melatonin treatment prevented cell apoptosis and necrosis in parallel with lipid peroxidation. 14 Zinc is also a strong antioxidant and it is acknowledged that it reduces oxidative stress and has neuroprotective effects.…”
Section: Introductionmentioning
confidence: 99%
“…There were no adverse effects if 0.5 mg ZnCl 2 (corresponding to 0.24 mg zinc) per day was given with the drinking water. We used this amount in our study because even lower amounts of zinc (0.11 mg per day) had shown physiological effects in a study evaluating the effect of melatonin on the production of nitric oxide in the mouse (Chen et al, 1999). A search of the literature yielded no data regarding the effect of a zinc surplus on NTDs in mice or rats.…”
Section: Diet and Supplementsmentioning
confidence: 96%
“…In this form, vitamin B6 is necessary for the conversion of tryptophan to serotonin. Zinc is also necessary for the production and modulation of melatonin, which helps regulate dopamine function (Sandyk 1990;Chen et al 1999), which is widely believed to be a key factor in attention-deficit/hyperactivity disorder (ADHD) and its treatment. In fact, Sandyk (1990) hypothesized that parasympathomimetic stimulants, at least amphetamine, work in ADHD partly through their effects on melatonin.…”
Section: Zinc and Brain Functionmentioning
confidence: 99%